Resilient cooperative control for optimal current sharing and voltage regulation of microgrid-based distribution network under FDI attacks - Wang, Biheng (Frontiers in Energy Research, 2022)
A secondary control framework of direct-current (DC) microgrid (MG) usually includes cyber threats in the hierarchical control architecture. This leads to the occurrence of some unfavourable phenomena, such as false data injection (FDI) attacks, which may pose a dramatic threat to the overall system. Motivated by this consideration, in this article, we consider the security secondary control problems for optimal current sharing and voltage restoration of an islanded DC MG under FDI attacks. To solve these problems, a resilient secondary control method is provided. Specifically, a resilient secondary controller is designed by introducing an adaptive parameter based on the adaptive technique. Then, a theoretical analysis method is provided to show that the designed resilient secondary controller can ensure optimal current sharing and voltage regulation under FDI attacks. To verify the developed resilient secondary control method, a simulation example is given by using the Matlab testing platform.